2009
DOI: 10.17221/956-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inorganic Salts on Acrylamide Formation in Cereal Matrices

Abstract: Abstract:The aim of the work was to compare the impact of different salts such as monovalent and divalent chlorides, hydrogencarbonates, phosphates and lactate on acrylamide formation in cereal model system during baking at 190°C for 9 min. Ammonium hydrogencarbonate promoted acrylamide production significantly. On the other hand, other inorganic salts lowered acrylamide content. Calcium chloride was the most effective with near to 90% acrylamide elimination ability. Sodium acid pyrophosphate, sodium as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…Acrylamide content was significantly reduced by 52%, 67%, 52% and 69%, 70%, 74% for CaCl 2 and MgCl 2 , respectively. Similar results have been reported for potato strips (Gökmen & Şenyuva, ), wheat‐based products (Levine & Ryan, ), and cereal matrices (Kukurová, Ciesarová, Bednáriková, & Marková, ), where the use of divalent cation derivatives in different forms is capable of reducing acrylamide levels. It has been recently suggested that adding divalent cations could provide high‐temperature stability to asparagine/matrix intermediates, thereby rendering the latter species unavailable for a reaction with carbonyl precursors to produce acrylamide (Göncüoğlu Taş, Hamzalıoğlu, Kocadağli, & Gökmen, ).…”
Section: Resultssupporting
confidence: 83%
“…Acrylamide content was significantly reduced by 52%, 67%, 52% and 69%, 70%, 74% for CaCl 2 and MgCl 2 , respectively. Similar results have been reported for potato strips (Gökmen & Şenyuva, ), wheat‐based products (Levine & Ryan, ), and cereal matrices (Kukurová, Ciesarová, Bednáriková, & Marková, ), where the use of divalent cation derivatives in different forms is capable of reducing acrylamide levels. It has been recently suggested that adding divalent cations could provide high‐temperature stability to asparagine/matrix intermediates, thereby rendering the latter species unavailable for a reaction with carbonyl precursors to produce acrylamide (Göncüoğlu Taş, Hamzalıoğlu, Kocadağli, & Gökmen, ).…”
Section: Resultssupporting
confidence: 83%
“…Graf et al (2006) noted that the addition NaHCO 3 at (2g) reduced AA by (70%) in biscuits. Also, Kukurova et al (2009) found that CaCl 2 , KCl and NaCl caused elimination AA formation by (90, 45 and 40%) respectively when salts were Values± standard deviation followed by the same letters in the same column are not significantly different at p ≤ 0.05 added individually at a concentration (0.1mmol/ kg) into model system during baking at 90 o C for 9 min. This may be due to the role of three salts in decreasing the water activity which influences the mechanism of acrylamide formation.…”
Section: Effect Of Salts and Hydrocolloids On Acrylamide Formation In...mentioning
confidence: 91%
“…In a fructose–asparagine chemical model, the formation of the Schiff base was prevented by Na + and Ca 2+ at concentrations equivalent to that of the reducing sugar (Gökmen & Şenyuva, 2007). Moreover, the capability of certain metal ions to decrease the pH of the surrounding medium suggests a high tendency for them to induce protonation of the amino group of asparagine, rendering it inactive in nucleophilic addition to a carbonyl group on molecules such as reducing sugars (Kukurová et al., 2009). Lower pH, however, could promote the formation of other hazardous compounds like 3‐monochloropropane‐1,2‐diol (Sadd et al., 2008) and HMF (Combs et al., 2013).…”
Section: Influence Of Nutritional Additives On Acrylamide and Age For...mentioning
confidence: 99%
“…Given the electrophilic/nucleophilic nature of the key participants in the MR, polar interactions represent a key part of the mechanism underlying the impact of mineral salts on AGE and acrylamide formation (Kukurová et al., 2009). Schiff bases, N ‐glycosyls, and related compounds have been identified to take part in the initial or intermediate stages of the formation pathways of these Maillard products (Stadler et al., 2002; Zyzak et al., 2003).…”
Section: Influence Of Nutritional Additives On Acrylamide and Age For...mentioning
confidence: 99%